The refounding of health systems in Latin America and the Caribbean. New hope from the South - Antonio Hernández Reyes (Social Medicine Publication Group, 2022)
Several decades after the first wave of state reforms, we can observe the neoliberal disaster manifested in an era of intense demonstrations, protests and struggles against exclusionary policies in Latin America and the Caribbean. In that first stage of state reform, loans from international organizations were promoted, serving as a basis for the construction of legal frameworks (constitutional reforms, laws, decrees, ministerial resolutions, among others),1,2. This facilitated the installation, in the political symbolic plane, of a structural crisis of the State in Latin American and Caribbean societies.